Gender and Sexuality Diversity in a Culture of Limitation Student and Teacher Experiences in Schools - Ferfolja, Tania (Routledge Critical Studies in Gender and Sexuality in Education, 2020)
Gender and Sexuality Diversity in a Culture of Limitation provides an outstanding and insightful critique of the ways that contemporary education is impacted by a range of political, social and cultural influences that inform the approaches that schools take in relation to gender and sexuality diversity. By applying feminist poststructural and Foucauldian frameworks, the book examines the ongoing impact of broader socio-cultural discourse on the lives of gender and sexuality diverse students and teachers. Beginning with an overview of the impact of how a culture of limitation is realised in Australia, the focus moves beyond this context to examine state and federal policies from comparable societies in countries including the USA and the UK and their effect on the production of knowledges and what's permissible to include in educational curriculum. This research-driven book thus provides a comparative, international overview of the current state of gender and sexuality diversity in schools, and convincingly demonstrates that despite some empowerment of gender and sexuality diverse individuals, silencing and marginalization remain powerful forces. This book will be of great interest to graduate and postgraduate students, academics, professionals, and policy makers interested in the field of gender and sexuality in education. It is essential reading for those involved in pre-service and in-service teacher education, diversity education, the sociology of education, as well as education more generally.